2001
DOI: 10.1006/jabr.2000.8670
|View full text |Cite
|
Sign up to set email alerts
|

Clifford Regular Domains

Abstract: Ž .The class semigroup of a commutative integral domain R is the semigroup S S R of the isomorphism classes of the nonzero ideals of R with operation induced by Ž . multiplication. A domain R is said to be Clifford regular if S S R is a Clifford Ž . semigroup, i.e. S S R is the disjoint union of the subgroups associated to the idempotent elements. In this paper we characterize the noetherian and the integrally closed Clifford regular domains and find some properties of an arbitrary Clifford regular domain. ᮊ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 14 publications
2
68
0
Order By: Relevance
“…Recently, it has been recalled in [27] to answer a question posed by Bazzoni in [4,5]. Next, the case of Inv * (D), with * of finite character, being a Riesz group satisfying Conrad's F-condition has been studied by Dumitrescu and Zafrullah [9] for the so-called t-Schreier domains.…”
Section: Lemma 55 Let a ∈ F(d) Be A * -Invertible Ideal Then The Fomentioning
confidence: 99%
“…Recently, it has been recalled in [27] to answer a question posed by Bazzoni in [4,5]. Next, the case of Inv * (D), with * of finite character, being a Riesz group satisfying Conrad's F-condition has been studied by Dumitrescu and Zafrullah [9] for the so-called t-Schreier domains.…”
Section: Lemma 55 Let a ∈ F(d) Be A * -Invertible Ideal Then The Fomentioning
confidence: 99%
“…Zanardo and Zannier proved that all orders in quadratic fields are Clifford regular domains [20] while Bazzoni and Salce showed that all valuation domains are Clifford regular [5]. The study of Clifford regular domains was then carried on by S. Bazzoni [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Since [3,Theorem 4.5]. To this end, she established an interesting relation between Clifford regularity and the local invertibility property: a domain has the local invertibility property (LIP) if each ideal I that is locally invertible (i.e., IR M is invertible, for each M ∈ Max(R)) is indeed invertible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…stable domains (cf. Bazzoni [2], Olberding [11], Sally-Vasconceles [13]), where the non-zero fractional ideals form a Clifford semigroup under multiplication (a Clifford semigroup is a disjoint union of groups). Artin has introduced an equivalence relation on the set of non-zero fractional ideals such that in certain integral domains the equivalence classes formed a group under multiplication.…”
Section: Introductionmentioning
confidence: 99%